Arm posture influences on regional supraspinatus and infraspinatus activation in isometric arm elevation efforts. (February 2019) - Alenabi, Talia; Whittaker, Rachel L.; Kim, Soo Y.; Dickerson, Clark R.
Abstract: This study aimed to evaluate the effect of arm posture on activation of the anterior and posterior regions of supraspinatus and the superior and middle regions of infraspinatus during resisted isometric arm elevations. Thirty-one healthy participants performed 18 isometric resistance exertions against a force cube in three elevation planes (flexion, scaption, abduction) and three elevation angles (30°, 90°, 150°) in maximal and sub-maximal resistance conditions. EMG data were obtained using four pairs of fine wire electrodes. The mean activation of each region and the activation ratios were compared across postures using ANOVAs. Supraspinatus anterior was significantly more active during abduction and scaption, and in higher elevation angles, while the posterior region showed similar activation levels across postures. Infraspinatus regions were more active during flexion with more relative activation of the infraspinatus superior at 90° flexion. The results suggest that regional activation of supraspinatus and infraspinatus should be considered for assessment and rehabilitation purposes. In any clinical setting where it is important to reduce the stress on the supraspinatus anterior, isometric flexion exercises performed with arm in low elevation angles could provide the opportunity to strengthen the posterior region of supraspinatus with limited stress on the anterior region. Beside external rotation exertions, resisted flexion tests may be useful for evaluation of infraspinatus regions.